(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In the process of drilling oil and gas wells, great requirements are placed on the properties and parameters of the drilling fluids. It is based on the fact that the wrong choice of properties and parameters of the solution in opening the formations with anomalously low formation pressure causes great complications.